Oral Fixation or Oral Corrective? A Response to Larry Hurtado - Iverson, Kelly R. ca. 20./21. Jh. (2016)
Over the last several decades, performance criticism has made significant headway as an interpretive method. However, in a recent issue of this journal, Larry Hurtado argues that the key assumptions of the movement ignore various historical realities regarding the use of texts in the ancient world. The following discussion offers a brief response to what Hurtado suggests are several oversimplifications'. The essay argues that rather than being a fixation' as Hurtado maintains, the renewed focus on orality and performance is a corrective that helps to provide a broader understanding of how biblical texts were typically experienced in the ancient world.
Keywords: Larry Hurtado; performance criticism; ancient media studies; Literacy; Orality